Fascicular turnover flap in the reconstruction of facial nerve defects: an experimental study in rats. Issue 3 (4th May 2019) - Uehara, Miyuki; Wei Min, Wu; Satoh, Moriaki; Shimizu, Fumiaki
Abstract: The purpose of this study was to assess the utility of a fascicular turnover flap for facial nerve repair and to investigate its possible application in the field of facial nerve repair using a rat model of facial paralysis. Twenty-four Wistar rats were used in this study. A left vibrissal muscle palsy model was established via excision of the buccal and marginal branches through a periauricular incision. In Group 1, the nerve gap was not reconstructed. In Group 2, the nerve gap of the marginal mandibular branch was reconstructed using an autograft, and in Group 3, the gap was reconstructed using a fascicular turnover flap. At 12 weeks after the operation, the nerve regeneration was assessed based on clinical, histopathological and electrophysiological evaluations. The functional recovery of the vibrissal muscle was observed with a fascicular turnover flap. The functional recovery of whisker movement was almost same between Groups 2 and 3 ( p  = .57). The histopathological examinations almost same result between Groups 2 and 3 ( p  = .17). The compound muscle action potential after reconstruction was also almost same between Groups 2 and 3 ( p  = .99). We found that the fascicular turnover flap could be applied to facial nerve gap reconstruction. However, further evaluations will be necessary to clarify its indication and mechanism in human.